Connecting Classroom, Clinic, and Context: Clinical Reasoning Strategies for Clinical Instructors and Academic Faculty. Issue 4 (2015) - Furze, Jennifer; Kenyon, Lisa K.; Jensen, Gail M.
Abstract : Background: Clinical reasoning is an essential skill in pediatric physical therapist (PT) practice. As such, explicit instruction in clinical reasoning should be emphasized in PT education. Key Points: This article provides academic faculty and clinical instructors with an overview of strategies to develop and expand the clinical reasoning capacity of PT students within the scope of pediatric PT practice. Achieving a balance between deductive reasoning strategies that provide a framework for thinking and inductive reasoning strategies that emphasize patient factors and the context of the clinical situation is an important variable in educational pedagogy. Teaching Implications: Consideration should be given to implementing various teaching and learning approaches across the curriculum that reflect the developmental level of the student(s). Deductive strategies may be helpful early in the curriculum, whereas inductive strategies are often advantageous after patient interactions; however, exposure to both is necessary to fully develop the learner's clinical reasoning abilities. Video Abstract: For more insights from the authors, see Supplemental Digital Content 1, available athttp://links.lww.com/PPT/A87 . Abstract : Supplemental Digital Content is Available in the Text.The authors describe strategies that can be used to develop clinical reasoning skills in physical therapist students both in the classroom and in clinic.